2019
DOI: 10.1039/c9sm01297d
|View full text |Cite
|
Sign up to set email alerts
|

Using optical tweezing to control phase separation and nucleation near a liquid–liquid critical point

Abstract: Laser-induced phase separation (LIPS) and LIPS and nucleation (LIPSaN) harness fluctuations near a liquid–liquid critical point using optical tweezing and underlie the process of nonphotochemical laser-induced nucleation (NPLIN).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 82 publications
(134 reference statements)
0
28
0
Order By: Relevance
“…Solubility phase diagram of the compound, the good solvent and the antisolvent provides a guideline for determination of the solvent ratio for crystallization. [ 10,19,26,29,30 ] Lately, researchers started looking closely into the interface between the two liquid phases, [ 31–33 ] where the mass transfer and heat transfer occur, directly influencing formation of the droplets and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Solubility phase diagram of the compound, the good solvent and the antisolvent provides a guideline for determination of the solvent ratio for crystallization. [ 10,19,26,29,30 ] Lately, researchers started looking closely into the interface between the two liquid phases, [ 31–33 ] where the mass transfer and heat transfer occur, directly influencing formation of the droplets and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…However, for macromolecules and molecular assemblies that have a larger α (resulting in larger potential well U trap ) optical trapping is feasible [7–9] . For example, Walton and Wynne clearly demonstrated phase separation and nucleation in a liquid mixture system (nitrobenzene/decane) by exploiting U trap [10, 11] . Sasaki and Masuhara et al.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] For example, Walton and Wynne clearly demonstrated phase separation and nucleation in a liquid mixture system (nitrobenzene/ decane) by exploiting U trap . [10,11] Sasaki and Masuhara et al also demonstrated the optical trapping of poly(N-isopropylacrylamide) (PNIPAM) in water facilitated by focusing a 1064 nm laser beam leading to the generation of F grad and a photothermal effect initiating a phase separation via coilglobule phase transition. [12][13][14][15] These trapping studies of molecular materials created new possibilities toward application of optical trapping for the nucleation and crystallization of organic and inorganic small molecules, [16,17] since optical trapping/optical tweezing can increase their local concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the field of (non-photochemical) laser-induced nucleation has expanded significantly [9][10][11][12][13][14][15] . The most recent work in this field has gone a step further by suggesting that the observed laser-induced effects have their origin in a laser-tweezing potential, or alternatively that they may stem from a stored electromagnetic energy that lowers the free energy [16][17][18] . Other studies of such passive chemical photonics includes non-resonant photocatalysis (alternatively termed dynamic Stark control), where intramolecular bond-breaking reactions have been catalysed in a plethora of molecules [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%